PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV UPTD SD NEGERI 28 PAREPARE - Usman; Yonathan S. Pasinggi; Mahaputri Amanda Faizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low motivation of students in the learning process is one of the problems that can hinder achieving optimal learning outcomes. Based on this problem, this study aims to describe students' learning motivation and to understand the effect of the Project Based Learning (PjBL) model on the learning motivation of fourth-grade students at UPTD SD Negeri 28 Parepare. The approach used is a quantitative approach with experimental research type, using a One Group Pretest-Posttest design. The research population is the students of UPTD SD Negeri 28 Parepare, with the sample being students of class IV.I. Data was collected through the distribution of learning motivation questionnaires. The data analysis technique used is the Paired sample t-test. The results of the inferential statistical analysis show a significance value (Sig. 2-tailed) of 0,001 < 0.05 and show that Tarithmetic > Ttable, namely 6,425 > 2,045 which means H0 is rejected and H1 is accepted. Thus, the conclusion of this study is that there is an increase in students' learning motivation before and after being given learning using the Project Based Learning (PjBL) model in the Science subject in class IV of UPTD SD Negeri 28 Parepare.